Nicotine alkaloids as antioxidant and potential protective agents against in vitro oxidative haemolysis. (5th January 2016) - Malczewska-Jaskóła, Karolina; Jasiewicz, Beata; Mrówczyńska, Lucyna
Abstract: The capacity of eleven nicotine alkaloids to reduce oxidative stress was investigated. In order to provide a structure-activity relationships analysis, new nicotine derivatives with a substituent introduced into the pyrrolidine ring were synthesized and investigated together with nicotine and its known analogs. All newly synthesized compounds were characterized by 1 H, 13 C NMR and EI-MS technique. The antioxidant properties of nicotine, its known analogs and newly produced derivatives, were evaluated by various antioxidant assays such 1, 1-diphenyl-2-picryl-hydrazyl free radical (DPPH ) scavenging, ferrous ions (Fe 2+ ) chelating activity and total reducing ability determination by Fe 3+  → Fe 2+ transformation assay. The protective effects of all compounds tested against 2, 2′-azobis(2-methylpropionamidine) dihydrochloride (AAPH) and tert -butyl hydroperoxide ( t -BuOOH)-induced oxidative haemolysis and morphological injury of human erythrocytes, were estimated in vitro . The results showed that nicotine alkaloids exhibited various antiradical efficacy and antioxidant activity in a structure- and a dose-dependent manner. In addition, the capacity of nicotine alkaloids to protect erythrocytes from AAPH- and t -BuOOH-induced oxidative haemolysis, was dependent on its incubation time with cells. Our findings showed that chemical and biological investigations conducted simultaneously can provide comprehensive knowledge concerning the antioxidant potential of nicotine alkaloids. This knowledge can be helpful in better understanding the properties of nicotine alkaloids under oxidative stress conditions. Graphical abstract: Highlights: Nicotine alkaloids (NA) protect human erythrocytes against oxidative injury. NA exhibit radical scavenging, Fe 3+ reducing and Fe 2+ chelating properties. Antioxidant potency of NA is structure- and dose-dependent.